Pembelajaran Berbicara Berbasis Pendidikan Karakter - Lusi Safitri; Khoirun Nisa; Rodiatul Hasanah Lubis (Universitas Dehasen Bengkulu, 2022)
Character-based speaking learning needs to be improved, because in reality there are still many students who find it difficult to speak when asked to speak in front of the class and find it difficult to use polite language when speaking. Many are still shy or choked up and break out in cold sweat when asked to speak in front of the class. If the situation is as above, the teacher must strive to provide opportunities for students to speak in turns using polite grammar in every learning process